Análisis a los estados financieros y estudio del capital de trabajo a la cooperativa de ahorro y crédito de profesionales de Loja, “Coodepro” Loja-Ltda, periodos 2010 - 2011 - Quizhpe salinas, Enma Josefina (2015)
The thesis regarding the "Analysis of Financial Statements and Working Capital Study the credit union Professionals Loja," Coodepro "period 2010-2011", was conducted in order to provide alternative solutions, to the difficulty of the lack of studies of this nature, where the lack of real economic and financial situation of the institution, hinders managers to take appropriate action. For its development was raised as a general objective of "Making an analysis to the Financial Statements and Working Capital Study the credit union Professionals Loja," Coodepro "period 2010-2011"; it was made in order to know the real financial and economic situation of the institution; and that compliance with the following specific objectives were established: Apply the methods of vertical, horizontal analysis, ratios or financial indicators to the states of the Cooperative to determine liquidity, solvency, profitability and indebtedness; Analyze the working capital using own indicators of economic activity of the institution; and finally prepare a report related to the Financial Statements Analysis and Study of Working Capital, the same that contains conclusions and recommendations that will contribute to a successful decision making by executives. The methodology used allowed the implementation of all the contents of the thesis and therefore to conclude a series of measures that are necessary for decision-making. Where he started from obtaining financial 5 statements and based on their analysis of the financial and economic structure it was made; and by applying financial indicators it was determined that the cooperative in the period under study, has a less favorable liquidity, which will ensure the timely cancellation of its short-term obligations, as it has $ 1.04 in the year 2010 and $ 1.07 in 2011, could also ascertain the total percentage of delinquency in the loan portfolio which is the 73.20% and 86.67% for each year respectively, which states that NPLs is extremely high, which is the weakness of the cooperative, which affects the activities of the credit department and greatly to other operating areas, harming the quality of the portfolio, while their assets, which is why in the final report analysis proceeds to provide alternatives aimed at improving the situation as well as other points at risk, such as debt shows that the majority of assets are funded by liabilities with 90.36% in 2010 and 88, 98% in 2011, so profitability indicates that the net income to total assets was a decrease of -2.62% in 2010, while for 2011 had an increase of 3.69%. Finally, conclusions and general recommendations that were made in order to provide information to the directors of the cooperative to make the best decisions and thus can provide greater security to the resources of its members present.